'I don't want to have a separated home': Reckoning family and return migration among married Nigerians in China. (17th December 2019) - Adebayo, Kudus Oluwatoyin
Abstract: The growing 'Africans in China' literature has documented the extent and extensiveness of flows from Africa to Chinese cities. However, return migration has not received much attention, and even less is known about the role of the family in return consideration. The article focuses on how married Nigerians reckon return and family in Guangzhou city using data from ethnographic observations and interviews with 25 participants. While the family is central to how married migrants think about return, the dynamics vary among the participants. Migrants whose spouses/children reside in Nigeria complain about being distant from their families and the challenge of unification and 'absentee fatherhood'. Nigerian couples that live in Guangzhou as a family consider the high cost of raising children and the future competitiveness of their children as 'China-educated' as factors in return calculations. Moreover, despite living with their husbands in China, some Nigerian women desire to return to Nigeria to improve their lives, but they did not embark on a return journey to avoid family separation. Among Nigerians in an interracial relationship with Chinese women, the feeling of (un)belongingness resonates in their return consideration owing to poor experiences with access to residence permit and social welfare. While integration issues impact on return migration of married Nigerians in Guangzhou, the transnational practices of the men suggest that a return behaviour would probably accompany return consideration.